1984
DOI: 10.1128/aac.26.1.26
|View full text |Cite
|
Sign up to set email alerts
|

New micromethod to study the effect of antimicrobial agents on Toxoplasma gondii: comparison of sulfadoxine and sulfadiazine individually and in combination with pyrimethamine and study of clindamycin, metronidazole, and cyclosporin A

Abstract: An in vitro method by which reagents, cells, and Toxoplasma gondii trophozoites are conserved (microniethod) was developed to quantitate the effect of antimicrobial agents on T. gondii. Sulfadoxine alone had no effect on T. gondii in vitro when evaluated with a macromethod, the new knicromethod, or visual inspection of Giemsa-stained preparations. Sulfadoxine combined with pyrimethamine inhibited T. gbndit more than did pyrimethamine alohe, but the combination of sulfadoxine plus pyrimethamine was slightly les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
52
2
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 10 publications
4
52
2
1
Order By: Relevance
“…gondii Parasites. Tachyzoites of the RH strain were maintained and used in experiments as described (12,13). GFP-, plastidlabeled RH strain parasites were kindly provided by B. Streipen and D. Roos (University of Pennsylvania, Philadelphia).…”
Section: Methodsmentioning
confidence: 99%
“…gondii Parasites. Tachyzoites of the RH strain were maintained and used in experiments as described (12,13). GFP-, plastidlabeled RH strain parasites were kindly provided by B. Streipen and D. Roos (University of Pennsylvania, Philadelphia).…”
Section: Methodsmentioning
confidence: 99%
“…Calcium and calmodulin antagonists have been shown to inhibit Plasmodium falciparum in vitro (21). We have shown previously that the calmodulin inhibitor cyclosporin A inhibits T. gondii in vitro (12). Verapamil was studied as the prototype calcium channel blocker, and trifluoperazine hydrochloride appears to be one of the more potent calmodulin inhibitors active against malaria (21).…”
mentioning
confidence: 99%
“…Since toxic effects from this therapy include bone marrow suppression and allergy to sulfonamides (especially in AIDS patients), there is currently a great need for alternative, effective antimicrobial agents. Therefore, we evaluated in vitro several antimalarial agents, as well as the calcium channel blocker verapamil and the phenothiazine trifluoperazine hydrochloride by using our previously described assay (12).…”
mentioning
confidence: 99%
“…In contrast, clindamycin has not prevented the replication of T. gondii in tissue culture systems (14,20).…”
mentioning
confidence: 99%
“…For example, a trial comparing the combination of clindamycin and pyrimethamine with the combination of sulfadiazine and pyrimethamine suggested that the efficacies of the two combinations were not significantly different (10). Clindamycin therapy has produced conflicting results in animal models of primary T. gondii infections (3,12,13,15,21,25) and in cell cultures challenged with T. gondii tachyzoites (14,20). Clindamycin has not been used to treat reactivated chronic infections in experimental animals.…”
mentioning
confidence: 99%